A Differential Oligopoly Game with Differentiated Goods and Sticky Prices - Luca Lambertini; Roberto Cellini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We investigate a dynamic oligopoly game where goods are differentiated and prices are sticky. We study the open-loop Nash equilibrium, and show that the latter equilibrium entails a larger level of steady state production as compared to the former; both equilibria entail a larger level of production in steady state than in static game. We also study the effects of price stickiness and product differentiation upon the steady state equilibrium allocation. We find that per-firm equilibrium output is increasing in both product differentiation and price stickmess.
Keywords: 330